ICTs for Development: What Prospects and Problems? - Mansell, Robin (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2004)
Investing in information and communication technology applications in developing countries is receiving considerable attention in policy debates. This paper reviews evidence of the digital divides that continue to exist, and then critically examines some of the optimistic views about the potential benefits of investment in information and communication technologies. Experiences of firms in several developing countries as they begin to consider and implement business-tobusiness electronic commerce provide a basis for the analysis. The evidence indicates that, while information and communication technology applications are playing a role in supporting the trading activities of firms in developing countries, there are many reasons for the absence of a wholesale shift from conventional trading practices to new forms of electronic commerce – and that these reasons are unlikely to change simply as a result of increased investment in the technologies.